A New Idea of Revitalization for Urbicide Crisis - Concetta Tavoletta (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2024)
«A manifest and violent opposition to the highest values of civilization», this is the definition that the Serbian Bogdan Bogdanovic gave to the term urbicide, which he coined to describe the atrocities of the War in the Balkans. Bogdanovic was mayor of Belgrade from 1982 to 1986 and has crystallized through his books the devastation that the territory suffered in those years. In his 1993 article for Lettera Internazionale he underlined how «it seems that there was less room for tenderness and love towards the city than there was space and stimulus for completely contrasting feelings: discomfort, revulsion, contempt and above all fear» and this can be found not only in the history of our civilization but also in the contemporary world. What remains of the cities are mostly skeletal, dormant and suffering elements, mirrors of abandonment and neglect. There are, however, further conditions of urbicide that sneakily creep into the contemporary panorama. This work proposes a reinterpretation of the phenomenon of urbicide by trying to describe good practices that seek to interpret destructive actions as a positive and alternative reality to the phenomenon.